The oxygen uptake-power regression in elite and club-level oarsmen: implications for the accumulated oxygen deficit - Romer, L. M.; Godfrey, R. J.; Jeukendrup, A. E. (2002)
It was hypothesised that the gradient of the O2-power regression and the O2 demand predicted for a supra-O2,max power output would be higher in elite rather than club-level athletes. Following ethics committee approval and written informed consent, 34 elite (GB National Squad) and 19 club-level oarsmen participated in the study. Tests were administered on a modified air-braked rowing ergometer (Concept IIC, Nottingham, UK). The test system (Avicon II, Berlin, Germany) incorporated a load cell for force measurement and a rotary transducer for the determination of stroke length. All participants performed a discontinuous incremental protocol that involved 30 W increments every 4 min and an increase in stroke rate of 2 strokes min-1 with each increment. Ventilatory and gas exchange parameters were measured breath-by-breath (Mijnhardt Oxycon Champion, Bunnick, Holland), and O2 during the 4th minute of each incremental stage was used to determine an individual O2-power regression. The regression was based on an average of four sub-lactate threshold determinations ranging from 59 ± 6 to 78 ± 7 % O2,max. Correlation coefficients (r) for individual regression equations averaged 0.996 ± 0.005 for all groups and were accepted as valid predictive equations (standard error of the estimate = 0.039 ± 0.032 l min-1). The amount of fat oxidised during sub-lactate threshold exercise intensities was estimated from measures of O2 and CO2 using stoichiometric equations (Péronnet & Massicotte, 1991). The gradient of the O2-power regression was greater in elite compared with club-level oarsmen (14.7 ± 2.4 vs. 13.4 ± 1.8 ml min-1 W-1, respectively; P ²le³ 0.05, independent samples t test). As a result, the predicted O2 demand at 438 W (the mean maximum power output sustained for 4 min) was also higher in elite than club-level oarsmen (6.85 ± 0.60 vs. 6.62 ± 0.44 l min-1, respectively; P ²le³ 0.05). The change in excess O2 cost due to fat metabolism relative to the change in power output over sub-lactate threshold exercise intensities yielded a gradient equal to 0.13 ± 0.02 ml min-1 W-1, which accounted for 9.7 % of the difference in O2-power slopes between the groups. The remainder of the difference in O2-power slopes was due to between-group differences in body mass. In conclusion, results of the present study suggest that greater rates of fat metabolism at lower intensities in elite oarsmen can contribute to differences in O2-power slopes determined across the same relative range of exercise intensities.